Stromal Protein Chloroplast Development and Biogenesis1 Is Essential for Chloroplast Development and Biogenesis in Arabidopsis thaliana - Chen, Weijie; Huang, Jingang; Chen, Shiwei; Zhang, Lin; Rochaix, Jean-David; Peng, Lianwei; Xin, Qiang (Frontiers in Plant Science, 2022)
Although numerous studies have been carried out on chloroplast development and biogenesis, the underlying regulatory mechanisms are still largely elusive. Here, we characterized a chloroplast stromal protein Chloroplast Development and Biogenesis1 (CDB1). The knockout cdb1 mutant exhibits a seedling-lethal and ivory leaf phenotype. Immunoblot and RNA blot analyses show that accumulation of chloroplast ribosomes is compromised in cdb1, resulting in an almost complete loss of plastid-encoded proteins including the core subunits of the plastid-encoded RNA polymerase (PEP) RpoB and RpoC2, and therefore in impaired PEP activity. Orthologs of CDB1 are found in green algae and land plants. Moreover, a protein shows high similarity with CDB1, designated as CDB1-Like (CDB1L), is present in angiosperms. Absence of CDB1L results in impaired embryo development. While CDB1 is specifically located in the chloroplast stroma, CDB1L is localized in both chloroplasts and mitochondria in Arabidopsis. Thus, our results demonstrate that CDB1 is indispensable for chloroplast development and biogenesis through its involvement in chloroplast ribosome assembly whereas CDB1L may fulfill a similar function in both mitochondria and chloroplasts.